Application and development of graphene functional materials in sports equipment: a review - Chun Lin; Cheng Li (Journal of Materials Science: Materials in Engineering)
Abstract The utilization of rubber and fibrous materials in the fabrication of sports equipment constitutes the foundation of this study. The judicious integration of materials science with the materials employed in sports equipment manufacturing is instrumental in propelling the field forward and enhancing athletic performance. A theoretical analysis of existing graphene technology and its applications to rubber and fibrous materials can provide a foundation for exploring the potential of graphene technology in sports equipment. This analysis can facilitate an organic integration of the materials (graphene) field and the sports field at the theoretical level, thereby promoting the application of graphene technology in the sports field. The present study aims to modify the substrate with graphene functional materials in rubber and fibrous materials to achieve the objective of enhancing the performance of sports equipment and improving athletes' performance in the manufacture of sports equipment.